Bending the Arc towards Equitable Partnerships in Global Health and Applied Training. Issue 1 (6th November 2019) - Martin, Nina A.; Kalbarczyk, Anna; Nagourney, Emily; Reich, Abigail; Hansoti, Bhakti; Kambugu, Andrew; Quinn, Thomas C.; Manabe, Yukari C.; Castelnuovo, Barbara
Background: Global health education has rapidly expanded in popularity, and many programs require applied practical experiences. Applied experiences are critical for global health training. Often a trainee from a high-income country travels to work with collaborators and partners in a low- or middle-income country. These experiences exist within partnerships between individuals and institutions that have varying objectives, including research, program implementation, or education. Attention is growing to ensure equity in these relationships in ways that are informed by the voices of collaborators and partners. Objectives: Understanding the experiences of LMIC collaborators in academic global health partnerships is essential. Our research aimed to capture views of our partners about factors impacting equitable global health partnerships. Methods: We conducted a small survey among global health collaborators and partners who host students on these experiences. Respondents were asked to rank enablers and barriers to equitable partnerships in priority order. Results were stratified by institutional affiliation and role. Results: Funding, time, engagement, and mutual opportunities for training are common enablers and barriers of global health partnerships. There were slight differences across different professional roles. Other reported factors that impact partnerships included language barriers, visa concerns, and identifying opportunities for collaboration. Conclusions: Our work highlights several barriers and enablers faced by partners that align with those reported across the global health education community. Equitable partnerships are possible and require substantial input at individual, interpersonal, and institutional levels. We reflect on two strategies to encourage partnership equity employed within our own work and discuss how these strategies can be applied more broadly.